Splice variants of CK1α and CK1α-like: Comparative analysis of subcellular localization, kinase activity, and function in the Wnt signaling pathway - Gybeľ, Tomáš; Čada, Štěpán; Klementová, Darja; Schwalm, Martin P; Berger, Benedict-Tilman; Šebesta, Marek; Knapp, Stefan; Bryja, Vítězslav (The Journal of biological chemistry, 2024)
Members of the casein kinase 1 (CK1) family are important regulators of multiple signaling pathways. CK1α is a well-known negative regulator of the Wnt/β-catenin pathway, which promotes the degradation of β-catenin via its phosphorylation of Ser45. In contrast, the closest paralog of CK1α, CK1α-like, is a poorly characterized kinase of unknown function. In this study, we show that the deletion of CK1α, but not CK1α-like, resulted in a strong activation of the Wnt/β-catenin pathway. Wnt-3a treatment further enhanced the activation, which suggests there are at least two modes, a CK1α-dependent and Wnt-dependent, of β-catenin regulation. Rescue experiments showed that only two out of ten naturally occurring splice CK1α/α-like variants were able to rescue the augmented Wnt/β-catenin signaling caused by CK1α deficiency in cells. Importantly, the ability to phosphorylate β-catenin on Ser45 in the in vitro kinase assay was required but not sufficient for such rescue. Our compound CK1α and GSK3α/β KO models suggest that the additional nonredundant function of CK1α in the Wnt pathway beyond Ser45-β-catenin phosphorylation includes Axin phosphorylation. Finally, we established NanoBRET assays for the three most common CK1α splice variants as well as CK1α-like. Target engagement data revealed comparable potency of known CK1α inhibitors for all CK1α variants but not for CK1α-like. In summary, our work brings important novel insights into the biology of CK1α, including evidence for the lack of redundancy with other CK1 kinases in the negative regulation of the Wnt/β-catenin pathway at the level of β-catenin and Axin.
Keywords: kaseinkinasa Ialfa; beta-katenin; Wnt3A Protein; protein Wnt3A; HEK293 Cells; lidé; Glycogen Synthase Kinase 3 beta; Wnt Signaling Pathway; HEK293 buňky; fosforylace; signální dráha Wnt; kinasa glykogensynthasy 3beta; alternativní sestřih; Casein Kinase Ialpha; kinasa 3 glykogensynthasy; Alternative Splicing; Glycogen Synthase Kinase 3; beta Catenin; Phosphorylation; Humans